Description and behaviour of Goniotropis kuntzeni larvae (Coleoptera: Carabidae: Paussinae: Ozaenini) and a key to genera of Paussinae larvae - Moore, Wendy; Giulio, Andrea Di (Zootaxa, 2006)
Goniotropis species are large, parallel-sided paussine beetles common in the New World tropics and ranging from southern Arizona to northern Argentina.  Specimens of Goniotropis kuntzeni Bänninger were collected in southern Arizona and larvae were reared under laboratory conditions.  The egg, first instar larva and second instar larva are described and illustrated, providing the first larval description for this genus.  Goniotropis larvae live in burrows that they construct and seal with their terminal disk (which is composed of modified urogomphi and dorsal plates).  They feed by trapping live insect prey with the moveable components of their terminal disk, and then they bring the captured prey into their gallery to consume.  Burrowing and feeding behaviours of Goniotropis kuntzeni larva closely resemble those previously described for Pachyteles species.  A key to the genera of paussine larvae is provided.